Tree growth, wood and bark water content of 28 Amazonian tree species in response to variations in rainfall and wood density - Dias Daniela P; Marenco Ricardo A (iForest - Biogeosciences and Forestry, 2016)
Pole diameter and wood density are variables commonly used in allometric equations to estimate tree biomass and carbon stocks in tropical forests. The effect of variations in tree water content on pole diameters is often disregarded in allometric equations. This study aimed to determine the effect of rainfall seasonality on tree growth, stem wood and bark water content and to assess the relationship between water content and wood density (dry mass to fresh mass volume ratio) in 120 trees from 28 species in a terra-firme rain forest in the central Amazon. In 2006, stem wood and bark water content were gravimetrically determined in the dry season (August-September) and rainy season (April-May). In the same year, growth in diameter was measured at monthly intervals in the 120 trees (DBH ≥ 10 cm) with dendrometric bands previously adapted to the tree. Mean wood water content was lower in the dry season than the rainy season. On the contrary, bark water content was higher in the dry season than in the rainy season. Wood densities higher than 0.75 g cm-3 were found in 64.3% of the trees. Trees with denser woods grew slower and had lower stem water content. Monthly rainfall did not affect tree growth in diameter, which was contrary to our initial expectation on the effect of rainfall seasonality on tree growth in central Amazonia. This finding supports the hypothesis that in central Amazonia, the mild dry season is not long enough to deplete soil water beyond the reach of the root system, which allows the trees to grow at quite constant rates over the year.